2012
DOI: 10.1056/nejmoa1110700
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neighborhood Characteristics with Bystander-Initiated CPR

Abstract: BACKGROUND For persons who have an out-of-hospital cardiac arrest, the probability of receiving bystander-initiated cardiopulmonary resuscitation (CPR) may be influenced by neighborhood characteristics. METHODS We analyzed surveillance data prospectively submitted from 29 U.S. sites to the Cardiac Arrest Registry to Enhance Survival between October 1, 2005, and December 31, 2009. The neighborhood in which each cardiac arrest occurred was determined from census-tract data. We classified neighborhoods as high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
136
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(144 citation statements)
references
References 31 publications
6
136
2
Order By: Relevance
“…[4,5] Despite clear evidence of benefit, The rates of bystander CPR vary between communities from 10 -75%. [14] Barriers to bystanders being willing to initiate CPR include socioeconomic deprivation, difficulty in diagnosing cardiac arrest, panic, fear of disease, fear of harming the victim or fear of performing CPR incorrectly. [15][16][17] Victim characteristics associated with less willingness for bystander CPR initiation include being unknown to the rescuer, appearing unkempt, evidence of drug use, the presence of blood, or vomit.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] Despite clear evidence of benefit, The rates of bystander CPR vary between communities from 10 -75%. [14] Barriers to bystanders being willing to initiate CPR include socioeconomic deprivation, difficulty in diagnosing cardiac arrest, panic, fear of disease, fear of harming the victim or fear of performing CPR incorrectly. [15][16][17] Victim characteristics associated with less willingness for bystander CPR initiation include being unknown to the rescuer, appearing unkempt, evidence of drug use, the presence of blood, or vomit.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, interesting existing data have demonstrated the influence of neighborhood socioeconomic status on the incidence and management of SCA. 44 However, in terms of SCA occurring in public places, this "time of exposition" (influence of neighborhood socioeconomic status) to neighborhood appears of limited value, especially in a city like Paris with very high population movement and consequently considerable heterogeneity in socioeconomic status. The extent to which the association between SCA and major train station may be driven by different (lower) socioeconomic status needs to be examined in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that OHCA cases happening in lower socioeconomic neighborhoods were less likely to receive BCPR [22][23][24][25][26][27] and survive 23,27,28 compared to those occurred at high socio-economic neighborhoods. But, one study showed an inverse relation between higher property values and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%